M.E. Dühring bouleverse la science (anti-Dühring) : tome 1. philosophie - Engels, Friedrich (Paris : Alfred Costes, 1949)
Bibliotheek Camille Huysmans
Frans
Monografie
Keywords: Dühring, Eugen; filosofie